Survival and Health-Related Quality of Life after Hospitalization for Necrotizing Soft Tissue Infections of the Upper Extremity: A Long-Term Outcome Study - Nawijn, Femke; Verhiel, Svenna H. W. L.; Nierich, Juliette; Eberlin, Kyle R.; Hietbrink, Falco; Chen, Neal C. (Journal of Hand and Microsurgery, 2020)
Introduction The main aim of the study was to investigate the survival and health-related quality of life (HRQoL) after hospitalization for necrotizing soft tissue infections (NSTIs) of the upper extremity.Materials and Methods A retrospective study with long-term follow-up of patients surviving NSTIs of the upper extremity was performed. Survival and HRQoL after hospital discharge were the primary outcomes. The HRQoL was measured using the 36-item Short Form (SF-36), EuroQoL-5D-5L (EQ-5D), Quick Disability of Shoulder, Arm and Hand (QuickDASH), and numeric rating scales (NRS) for satisfaction with appearance and pain.Results A median of 6.5 years after hospitalization, 81% of the 108 patients survived. The response rate was 45% (n = 38). The SF-36 score was 80 (interquartile range [IQR]: 58–91), the EQ-5D score 1.4 (IQR: 1.2–2.2), the EuroQoL-Visual Analog Scale score 77 (IQR: 67-90), the QuickDASH score 13.6 (IQR: 2.3-30.7), the NRS for satisfaction with appearance 8 (IQR: 7–9), and NRS for pain 1 (IQR: 0-5).Conclusion Six-and-a-half years after the NSTI, 81% of the patients were still alive. General health prior to the NSTI mainly influenced the risk at secondary mortality. In surviving patients, the HRQoL varied widely, but was adversely affected by female sex, intravenous drug use, NSTI type I or III, and longer length of hospital stay.
Keywords: necrotizing soft tissue infection; necrotizing fasciitis; quality of life; survival; upper extremity